2007
DOI: 10.1353/hpu.2007.0117
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Engagement in Smoking Cessation Counseling among Rural Smokers

Abstract: This study demonstrates that smokers will remain engaged in long-term counseling designed to address the chronic nature of nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The other study sampled pregnant and/or postpartum smokers recruited from rural Midwest Women Infant and Children Nutritional Supplement clinics (Bullock et al, 2009). Neither intervention resulted in a significant change in smoking rates, though Cupertino et al (2007) found that participants with lower income, lower educational attainment, and those lacking insurance were less likely to remain engaged in the 2-year telephone cessation intervention in this study. The third study had a total sample size of 68 which included 51 women (75%) and tested short-term effectiveness of an Internet-based abstinence reinforcement of smoking cessation in rural Kentucky smokers (Stoops et al, 2009).…”
Section: Findings From Randomized Trials/intervention Studiesmentioning
confidence: 66%
“…The other study sampled pregnant and/or postpartum smokers recruited from rural Midwest Women Infant and Children Nutritional Supplement clinics (Bullock et al, 2009). Neither intervention resulted in a significant change in smoking rates, though Cupertino et al (2007) found that participants with lower income, lower educational attainment, and those lacking insurance were less likely to remain engaged in the 2-year telephone cessation intervention in this study. The third study had a total sample size of 68 which included 51 women (75%) and tested short-term effectiveness of an Internet-based abstinence reinforcement of smoking cessation in rural Kentucky smokers (Stoops et al, 2009).…”
Section: Findings From Randomized Trials/intervention Studiesmentioning
confidence: 66%
“…stronger longitudinal engagement with individuals participating in behavior change programs and avoidance of attrition are thought to be related to outcomes. 11,12 the requirement of regular in-person contact, however, increases program attrition, reducing the opportunity for long-term engagement. 13 interactive communications technology, such as short message system (sMs) text messages, offers a means of engagement between inperson visits without significantly increasing participant burden.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several investigators have introduced a program of research to examine treatment in rural primary care practices in Kansas Cupertino et al, 2007Cupertino et al, , 2008. To date, their work indicates that patients are willing to enroll in a disease-management approach to treat nicotine dependence.…”
Section: Rural Smokersmentioning
confidence: 99%